Digital Education as an Innovative Strategy for Stunting Prevention: A Literature Review - Salis Miftahul Khoeriyah; Rika Monika; Firmina Theresia Kora; Ega Lestari; Risti Tamara Tahanora (Indonesian Journal of Global Health Research, 2025)
Stunting is a public health problem that is still high in Indonesia and other developing countries. Prevention efforts require an innovative approach, one of which is through digital education that is able to reach targets quickly and effectively. This article aims to examine the various digital education interventions used in stunting prevention and analyze their effectiveness based on evidence from original research. This study is a review of the narrative literature on 11 original research articles published between 2020–2025. A total of 372 articles were initially identified through database searches (PubMed, ScienceDirect, Google Scholar, Garuda, and ResearchGate). After applying the inclusion and exclusion criteria and removing duplicates, 11 articles met the eligibility criteria and were included in the analysis. Article selection follows the PICOS criteria and the PRISMA process. Digital education in the form of mobile applications, voice and text messages, and online media has been proven to improve nutrition knowledge, change feeding behavior, and improve children's nutritional status. The effectiveness of interventions is greatly influenced by consistent message exposure, support of health cadres, and readiness of digital infrastructure. Digital education is a relevant and adaptive strategy in stunting prevention. Integration with community and cross-sector approaches is critical to ensuring the success and sustainability of the program.